Heat-unit accumulation as a measure of adaptablity in chickpea (Cicer arietinum) - Bello, L L; Ojo, A A; Kalu, B K (The Indian Journal of Agricultural Sciences, 2005)
An experiment was conducted during 1999 and 2000 to study heat units accumulation in ’Ex-Punjab’ chickpea (Cicer arietinum L.) at a southern Guinea Savanna location, Nigeria. The experiment had 3 planting dates, starting in July and ending in August each year. The planting was done at 2 weeks interval and 2 intra-row spacings (20 cm and 25 cm). The combined analysis revealed that planting date and year effects were significant (P &lt 0.05). Planting date x spacing interaction and intra-row spacing were not significant (P&gt 0.05). In both years, there was a progressive reduction in number of days (7) and heat units (157) as planting was delayed from 6 July to 10 August. The planting during 20 and 27 July was found best with higher yield (210.5 and 214.2 kg/ha) in both years. The chickpea adapted very well to the system of cropping, although the yield was low. In both years, the pods and seeds/plant were comparable except 2000 August planting that suffered considerably from early cessation of rains. The results indicated that about 2189 heat units and 248 mm rainfall would be required for chickpea production at this location. Significant positive correlation was observed between pods/plant and seed yield (r=0.85). Pods/plant could be used as indirect selection criterion to pick high-yielding lines.